The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s1415-43662007000100007
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial de plantas daninhas em dois sistemas de manejo de solo

Abstract: RESUMOEstudos sobre a distribuição espacial das plantas daninhas são importantes no contexto agronômico e ambiental. O objetivo deste trabalho foi descrever a distribuição espacial de plantas daninhas em dois sistemas de manejo de solo. O estudo foi realizado em um Latossolo Vermelho distroférrico, em Campo Mourão, PR, utilizado em sistema de plantio direto (PD) e preparo convencional do solo (PC). Estabeleceu-se uma malha referenciada em coordenadas x e y, totalizando 128 pontos amostrais. Avaliou-se a biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
7
0
4
Order By: Relevance
“…Schaffrath et al (2007) estudiando la variabilidad espacial de malas hierbas en diferentes sistemas de manejo del suelo encontraron valores de CV entre 86,05% y 168,85% para la siembra directa y entre 74,73% y 81,72% para el cultivo convencional.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Schaffrath et al (2007) estudiando la variabilidad espacial de malas hierbas en diferentes sistemas de manejo del suelo encontraron valores de CV entre 86,05% y 168,85% para la siembra directa y entre 74,73% y 81,72% para el cultivo convencional.…”
Section: Resultados Y Discusiónunclassified
“…De acuerdo con Schaffrath et al (2007) el manejo del suelo interfiere sobre la variabilidad espacial de malas hierbas en suelos cultivados con praderas. Mosquera Losada et al (1999) describen que algunas especies de malas hierbas se mantienen inertes en el sistema agrícola hasta que tienen condiciones favorables para su pleno desarrollo.…”
Section: Correlación Espacial Entre Malas Hierbas Enunclassified
“…Statistical methods such as: semivariogram, kriging has been used to study the spatial variability of soil attributes, taking into account the understanding of the processes of soilorganism interaction (SCHAFFRATH et al, 2007). VIEIRA (2000) has demonstrated that in nearest locations amongst themselves are more similar than those that are further away.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding weed occurrence, the systems are also influential, mainly in terms of the higher weed density and biomass in conventional tillage. In no-tillage, the influence is verified in the larger diversity of the infesting community, with lower biomass (Schaffrath et al, 2007). Therefore, weeds behave similarly to crop plants, which tend to have a lower yield in more compacted soils (Freddi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%